Summaries of cases dealt with by the almoner - Brimmell, Maud E.
1903-09-28 1903 1900s 5 pages such an influence over her that she is anxious & willing to submit to the discipline & probation of a Rescue Home. 4. 18 mths f.v. F.C. 9 boy with early hip disease - F. withdraws application to C.O.S. when asked to pay 5/- a wk for boy. He had understated his earnings & was altogether most difficult Strong personal influence was brought to bear on F. & M. with the result that they paid the cost of boy's treatment for the whole year & on his return home cured are anxious & careful of him in a very different way from before - F. & M. have both been in the habit of working but the M. has determined to remain at home for the boy's sake. The case was a slow & disappointing one, & I believe nothing but the confidence which had been established between the parents & their friend would have kept them from losing heart I would contrast the dealing in this case with the two following. 5 3 wks. f.v. W.M. 3. tuberculous hip disease. Mother & grandparents highly respectable people all doing their best to keep the house & children while F. is out of work. Enquiries prove him to be unsteady - case is at once marked off as unsuitable for charitable help without any effort being made to see the Father or to come to any satisfactory arrangement with the relatives. Before the case is reported to me the I.C.A.A. have it in hand, & the responsibility is taken out of the parents hands, & the chance of influencing the 378/IMSW/A/1/2/44